2017 IEEE 85th Vehicular Technology Conference (VTC Spring) 2017
DOI: 10.1109/vtcspring.2017.8108580
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Noise Variance Decoder for Uncoordinated Multiple Access in VLC

Abstract: Abstract-In a visible light communications system (VLC), light sources are responsible for both illumination, communications and positioning. These light sources inevitably interfere each others at the receiver. To retain the appealing advantage that VLC systems can reuse existing lighting infrastructure, using an extra network to control or synchronize the light sources should be avoided. This paper proposes an uncoordinated multiple access scheme for VLC systems with positioning capability. The proposed sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…3) Simulation results are obtained and have shown that the proposed scheme significantly outperforms existing schemes in the literature in terms of the BER and system throughput when they are applied to a DAS. This paper improves the preliminary result in [1] and has the following significant differences: i) This paper proposes a novel scheme, in which receivers can obtain an unbiased channel estimate per each codeword duration despite the transmit data randomness. Channel estimation rate is therefore much higher than the rate allowed in [1].…”
Section: B Contributionsmentioning
confidence: 78%
See 3 more Smart Citations
“…3) Simulation results are obtained and have shown that the proposed scheme significantly outperforms existing schemes in the literature in terms of the BER and system throughput when they are applied to a DAS. This paper improves the preliminary result in [1] and has the following significant differences: i) This paper proposes a novel scheme, in which receivers can obtain an unbiased channel estimate per each codeword duration despite the transmit data randomness. Channel estimation rate is therefore much higher than the rate allowed in [1].…”
Section: B Contributionsmentioning
confidence: 78%
“…This paper improves the preliminary result in [1] and has the following significant differences: i) This paper proposes a novel scheme, in which receivers can obtain an unbiased channel estimate per each codeword duration despite the transmit data randomness. Channel estimation rate is therefore much higher than the rate allowed in [1]. Simulation results in this paper illustrate a case that a received vector with length equal to 34 is sufficient for good channel estimation.…”
Section: B Contributionsmentioning
confidence: 78%
See 2 more Smart Citations
“…Almost all of them are based on the underlying assumption that the receiver can differentiate among light sources: this can be realized by having the LEDs working in a transmission multiplexing scheme such as Time Division Multiple Access (TDMA) and Frequency Division Multiple Access (FDMA), which are common technologies. Discussions of the advantage and disadvantage of these multiple access schemes for VLC can be found in [14].…”
Section: Related Workmentioning
confidence: 99%